Mediating effects of english proficiency on the relationships between reading strategies, vocabulary size and reading comprehension among Saudi high school EFL learners - Alzahrani, Saeed (2021)
The ability to read and comprehend a text has long been considered critical for achieving success in academic studies. While a myriad of studies have investigated the components that affect learners’ reading comprehension and use of reading strategies, the literature pertaining to reading comprehension among EFL Saudi adolescents is rather scarce. The scarcity of research about this populations’ ability in reading comprehension, as well as the factors that may facilitate and hinder their reading comprehension makes this study particularly important. To address this gap, this study examined the mediation effects of English proficiency on the relationships between vocabulary size, reading comprehension strategies and reading comprehension achievement among Saudi high school EFL learners. The theories underpinning this study are bottom-up, top-down, and interactive models (Aebersold &Field, 1997). This study, which employed the quantitative design, involved 200 Saudi EFL school learners. Data were gathered quantitatively and qualitatively. Specifically, two questionnaires and two tests namely, the reading strategies questionnaire (SORS), the vocabulary size test (VST), the reading comprehension test, and the proficiency test were used for the quantitative data collection. Qualitative data collection methods, namely, interviews and focus group discussion (FGD) were also used for data gathering. The quantitative data were analysed using both descriptive statistics and inferential statistics using PLS-SEM, whereas the qualitative data was analysed using thematic analysis. The result of the mediation effect analysis indicated that all independent variables (vocabulary size, global reading strategies, problem-solving reading strategies and support reading strategies) through English proficiency as a mediator on dependent variable (reading comprehension) were statically significant. Therefore, the result showed that English proficiency mediates the relationships between vocabulary size, global reading strategies and support reading strategies with reading comprehension. Moreover, the results of the study revealed that the problem-solving strategy was the most frequently used in reading comprehension among the Saudi EFL school learners, followed by the global reading strategies and support reading strategies. The majority of the participants also had a very low vocabulary size and proficiency level. Yet, there was a significant difference in the vocabulary size across proficiency level. The results also showed that three reading strategies had a positive and significant relationship with vocabulary size, specifically the support reading strategies, which recorded the highest correlation coefficient. The implications of the present study provided insights about the reading comprehension challenges encountered by EFL Saudi high school learners. The study also contributed to the understanding of the factors that may facilitate and hinder reading comprehension among EFL learners. Also, the above results provide several useful insights for Saudi ESL teachers, curriculum designers, academic coordinators, and the Saudi Ministry of Education in terms of improving reading comprehension among Saudi high school EFL learners. The study presented some recommendations, the need for more research of EFL reading in Saudi Arabia and, some recommendations which related to reading materials, and reading strategy instruction.